PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STRATEGI SPOTLIGHT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMP N 8 PEKANBARU - Nur Ambiah Aritonang; Mitri Irianti; Zuhdi Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research aims to to find out the learning motivation improvement of SMP Negeri 8 Pekanbaru students at the application of cooperative learning model of spotlight strategy. This research is pre-experiment of one group pretest-posttest. The subjects of this research are the 39 students of class VII.3 SMP Negeri 8 Pekanbaru. The design of this research is pre-experiment using ARCS motivation learning questionnaire as data collecting instrument.Data were analyzed descriptively using N Gain. The relults of this study indicate an increase in student learning motivation by applying the cooperative learning model of spotlight in every ARCS indicator.Key words: ARCS, Spotlight Strategy, Learning Motivation.